Internalizing Aswaja Values to Develop Students’ Moderate Character in Indonesian Islamic Boarding Schools - Firdaus; Ibnu Imam Al Ayyubi; Namiyah Fitriani; Rabiatul Nadawiyah (Sekolah Tinggi Ilmu Tarbiyah Bustanul Ulum Lampung Tengah, 2026)
The issue of religious extremism and intolerance has become a significant challenge in contemporary Islamic education, particularly in shaping students’ religious character. Islamic boarding schools (pesantren) play a strategic role in instilling moderate Islamic values through religious learning traditions and cultural practices. This study aims to describe the internalization of Ahlussunnah wal Jama’ah (Aswaja) values tawasuth (moderation), tawazun (balance), tasamuh (tolerance), and i’tidal (justice) in developing the moderate character of students at Simpay Hurip Al-Musri’ Islamic Boarding School as a non-formal salafi pesantren. The study employed a descriptive qualitative approach with a case study design. Research participants included the kiai, teachers, and students selected through purposive sampling. Data were collected through in depth interviews, observations, and documentation and analyzed using the Miles and Huberman model. The novelty of this research lies in revealing the internalization of Aswaja values in a non-formal salafi pesantren without a formal curriculum but implemented systematically through pesantren culture, exemplary leadership, and traditional learning activities. The findings show that this process fosters open, tolerant, and dialogical attitudes among students.